Hubungan Dukungan Keluarga Dengan Kualitas Hidup Penderita Filariasis Di Kabupaten Aceh Utara - Cut Nana; Rizka Sofia; Wizar Putri Mellaratna (Journal of Pharmaceutical and Sciences, 2026)
Background: Lymphatic filariasis is a neglected tropical disease caused by Wuchereria bancrofti, Brugia malayi, and B. timori infection, leading to permanent lymphatic dysfunction with lymphedema and hydrocele as major complications. This chronic condition significantly impairs patients' quality of life (QoL), necessitating adequate family support for disease management and psychosocial adaptation. North Aceh Regency represents one of the highest filariasis-endemic areas in Aceh Province, Indonesia, yet empirical evidence on the relationship between family support and QoL among filariasis patients in this specific cultural context remains limited. Objective: This study aimed to analyze the relationship between family support and quality of life among lymphatic filariasis patients in North Aceh Regency, Indonesia. Methods: A descriptive-analytical cross-sectional study was conducted from March to December 2023 involving 54 filariasis patients selected through total sampling from 21 sub-districts in North Aceh Regency. Data were collected using the Perceived Social Support from Family (PSS-Fa) questionnaire and the WHOQoL-BREF instrument through structured interviews. Statistical analysis employed Fisher's exact test to examine the association between family support and QoL, with significance set at p<0.05. Results: The majority of respondents were of productive age (66.7%), female (59.3%), and employed (61.1%). Family support was predominantly strong (70.4%), while overall QoL was mostly moderate (48.1%). Dimensional analysis revealed good physical health (42.6%) and psychological (46.3%) domains, whereas social (44.4%) and environmental (63.0%) domains were moderate. Fisher's exact test demonstrated a significant relationship between family support and quality of life (p=0.000), with 70.3% of respondents with strong family support reporting good-to-moderate QoL compared to only 3.7% with weak family support. Conclusion: There is a significant positive association between family support and quality of life among filariasis patients in North Aceh Regency. Strengthening family-based support systems may serve as an effective strategy to improve QoL outcomes in filariasis-endemic communities, particularly within the socio-cultural context of Acehnese society.